Microstructure and mechanical properties of laser-arc hybrid welding joint of GH909 alloy. (June 2016) - Liu, Ting; Yan, Fei; Liu, Sang; Li, Ruoyang; Wang, Chunming; Hu, Xiyuan
Abstract: In this paper, laser-arc hybrid welding of 10 mm thick low-thermal-expansion superalloy GH909 components was carried out to obtain a joint with good performance. This investigation was conducted using an optical microscope, scanning electron microscope, energy diffraction spectrum and other methodologies. The results showed that weld joints with a desirable wineglass-shaped weld profile can be obtained employing appropriate process parameters. The different grains in between the upper central seam and the bottom seam were associated with the temperature gradient, the pool's flow and the welding thermal cycle. MC-type carbides and eutectic phases (γ+Laves) were produced at grain boundaries due to the component segregation during the welding process. In addition, γ′ strengthening phase presented in the interior of grains, which kept a coherent relationship with the matrix. The lowest hardness value occurred in the weld center, which indicated that it was the weakest section in the whole joint. The average tensile strength of the joints reached to 632.90 MPa, nearly 76.84% of the base metal. The fracture analysis revealed that the fracture mode of the joint was ductile fracture and the main reason for joint failure was as a result of the occurrence of porosities produced in the weld during the welding process. Highlights: It is a new process for laser-MIG hybrid welding joint of 10 mm GH909 alloy. The microstructure and mechanical properties of welded joints has been studied. A new method is applied to deal with the overlap.